Phenotypic and functional analyses of NK and NKT-like populations during the early stages of chikungunya infection - Thanapati, Subrat; Das, Rumki; Tripathy, Anuradha S. (Frontiers in Microbiology, 2015)
The aim of this study was to characterize NK (CD56+CD3−) and NKT-like cell (CD56+CD3+) responses early after chikungunya infection. Expression profiling and functional analysis of T/NK/NKT-like cells were performed on samples from 56 acute and 31 convalescent chikungunya patients and 56 control individuals. The percentages of NK cells were high in both patient groups, whereas NKT-like cell percentages were high only in the convalescent group. The percentages of NKp30+CD3-CD56+, NKp30+CD3+CD56+, CD244+CD3-CD56+, and CD244+CD3+CD56+cells were high, whereas the percentages of NKG2D+CD3-CD56+ and NKG2D+CD3+CD56+cells were low in both patient groups. The percentages of NKp44+CD3-CD56+ cells were high in both patient groups, whereas the percentages of NKp44+CD3+CD56+ cells were higher in the acute group than in convalescent and control groups. The percentages of NKp46+CD3-CD56+ cells were high in both patient groups. Higher percentages of perforin+CD3-CD56+ and perforin+CD3+CD56+ cells were observed in acute and convalescent patients, respectively. Higher cytotoxic activity was observed in acute patients than in controls. IFN-γ expression on NK cells of convalescent patients and on NKT-like cells of both patient groups was indicative of the regulatory role of NK and NKT-like cells. Collectively, these data showed that higher expression of activating receptors on NK/NKT-like cells and perforin+ NK cells in acute patients could be responsible for increased cytotoxicity. The observed expression of perforin+ NK cells in the acute phase and IFN-γ+ NKT-like cells in the subsequent convalescent stage showed that NK/NKT-like cells mount an early and efficient response to chikungunya virus. Further study of the molecular mechanisms that limit viral dissemination/establishment of chronic disease will aid in understanding how NK/NKT-like cells control chikungunya infection.